Peran Guru Ngaji dalam Meningkatkan Prestasi Belajar Siswa di Lembaga Pendidikan Al-Gafari - Muhamad Zaril Gapari (Pendidikan Al-Gafari, 2024)
The Qur’an teacher, which in religious terms is often called ustadz, mudarris, mu’alim, and mu’addib, is a term for someone who teaches Islamic knowledge to the community. Other nicknames that are more familiar to the ears of the Indonesian people are guru, lecturer, tutor, and kiyai. This study aims to determine the role and obstacles of the Qur’an teacher in improving student learning achievement at the Al-Gafari Educational Institution. This study uses the Qualitative Descriptive method to obtain information on the role and obstacles of the Qur’an teacher in improving student learning achievement at the Al-Gafari Educational Institution. This study uses unstructured and structured interviews by researchers with the Head of the Institution, Qur’an teacher, Parents of Students, and Students of the Al-Gafari Educational Institution. The results of this study show that there are several roles of the Koran Recital Teacher, including the Qur’an Recital Teacher as someone who provides the basis for students to become proficient in reading and writing the Koran, the Qur’an Recital Teacher as a director, instiller and guide for students in having good morals towards parents, teachers and peers, the Qur’an Recital Teacher as a motivator for students to continue learning in depth the Qur’an and Hadith, the Qur’an Recital Teacher as a controller in the learning process at the Qur’an recitation place, the Koran Recital Teacher as a mediator and solution provider in religious problems, especially in problems with the procedures for reading the Koran and Hadith properly and correctly, the Qur’an Recital Teacher as a role model for his students and, the Qur’an Recital Teacher as an instiller of discipline in students. Meanwhile, the obstacles faced by Qur’an teachers in improving student learning achievement at Al-Gafari Educational Institution are the lack of interest and enthusiasm of students in reciting the Qur’an, students are too busy playing with their cellphones so they are negligent in reciting the Qur’an, the students' residential environment is far from the place of reciting the Qur’an, the lack of support and motivation from the student's parents so that students are lazy to go to reciting the Qur’an, Qur’an teachers cannot be too firm in responding to students who are lazy and naughty in reciting the Qur’an because of human rights.